Continuity of the parks: fantastic elements and fusion of possible worlds - Rocamora, María del Pilar Miranda; Guarin, Jorge Orlando Gallor (Revista do Colóquio, 2021)
This paper analyses a classic of Latin American short fiction and suggests one of the possible readings that the text offers. This reading will be based on two very defined and complementary paths. The first is the analysis that allows the theory of Possible Worlds and the second takes into account one of the values ​​that Julio Cortázar most appreciated in the reader, our fantasy, delimited in this case by the story, which allows people to participate as reader-accomplices.